2006
DOI: 10.1002/anie.200601264
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally Strong Electronic Communication through Hydrogen Bonds in Porphyrin–C60 Pairs

Abstract: Hooking up: Self‐assembly of a porphyrin amidine and fulleropyrrolidine carboxylic acid based on a two‐point amidinium–carboxylate motif leads to supramolecular dyads of high stability (Ka≈107 M−1 in toluene/acetonitrile (9:1)). The synergy of the hydrogen bonds and electrostatic interactions has been shown to be particularly beneficial in terms of electronic coupling between both electroactive components of the dyads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(69 citation statements)
references
References 56 publications
(6 reference statements)
1
68
0
Order By: Relevance
“…Moving to a more competitive medium, isothermal calorimetry (ITC), 13 C NMR experiments and molecular dynamics (MD) simulations all showed strong benzoate anion binding in 95 : 5 acetonitrile : water ( K a ∼ 2900 M –1 , 1 H NMR experiments were precluded by disappearance of N–H resonances in this solvent mixture, see ESI† for details of anion recognition experiments). 18 Negligible association was observed between 1 + and chloride anion in this competitive aqueous medium.…”
Section: Resultsmentioning
confidence: 82%
“…Moving to a more competitive medium, isothermal calorimetry (ITC), 13 C NMR experiments and molecular dynamics (MD) simulations all showed strong benzoate anion binding in 95 : 5 acetonitrile : water ( K a ∼ 2900 M –1 , 1 H NMR experiments were precluded by disappearance of N–H resonances in this solvent mixture, see ESI† for details of anion recognition experiments). 18 Negligible association was observed between 1 + and chloride anion in this competitive aqueous medium.…”
Section: Resultsmentioning
confidence: 82%
“…Photoexcitation of the fullerene chromophores to their 1.76-eV excited state is followed, in one of the three forms of 11, by a charge separation process generating a 1.15-eV radical ion pair state. On average, this state perdures for at least 1.5 s, which is comparable to the performance of other noncovalent C 60 -based hybrids (in which electron transfer occurs basically via through-space interactions) (14,15,(31)(32)(33) and is superior to that of typical covalent C 60 -exTTF conjugates (25)(26)(27)(28). The structure of 11 in principle allows its extension to form a nanotubular battery along which electron donors and electron acceptors alternate and also suggests the possibility of designing molecular switches based on dynamic control of interconversion between the electroactive isomer 11-Z and the inactive isomers 11-X and 11-Y.…”
mentioning
confidence: 52%
“…In fact, charge separation caused by photoexcitation of exTTF in either heterodimer 11 or homodimers of 10 is negligible, and an efficient electron transfer is precluded by the short lifetime (Ϸ0.86 ps) of the transient species with a spectral peak at 605 nm (SI Fig. 8) (31).…”
mentioning
confidence: 99%
“…Guldi et al reported a set of two-point amidinium-carboxylate H-bonded C 60 -porphyrin ensembles (8) [62]. between zinc porphyrin and C 60 was calculated.…”
Section: Electron Transfer Based On Double and Triple Hydrogen Bondingmentioning
confidence: 99%